Atrocity, deviance, and submarine warfare : norms and practices during the world wars - Ben-Yehuda, Nachman (Configurations (Ann Arbor, Mich.), 2013)
In an era of changing ethics, the submarine has inaugurated a new type of unrestricted naval warfare.